Formação de nanocristais de hidroxiapatita durante a síntese de um biovidro quartanário do tipo SiO2.Na2O.CaO.P2O5 via sol-gel - Santos, Silmara Caldas (2016)
The sol-gel process used in obtaining bioactive glasses provide suitable conditions for the precipitation of hydroxyapatite nanocrystals below the glass transition temperature (Tg), even before they were immersed in biological fluids. However, because it is an ordering short, there is a great difficulty in proving its existence via the usual methods of characterization.There is evidence that the sol-gel process used to obtain bioactive glasses provides), and even before being immersed in biological fluids. Because of its short-range order, there is a great difficulty in proving its existence via the usual methods of characterization. Thus, the aim of this study was to understand the process involved in the formation of this nanocrystalline phase on the bioactive glass using Rietveld refinement on data from X-ray diffraction and high-resolution transmission electron microscopy (HRTEM); and how this glass behave on dissolution/precipitation essays. In addition, MgO oxide was used as probe to confirm the presence of apatite phase. Nanocrystalline apatite domains were observed after thermal treatment, even at temperatures below the Tg. The formation of this phase is directly related to the initial separation of calcium nitrate and triethyl phosphate (TEP) from amorphous silicate clusters during the drying process. After heat treatment at 300oC, calcium nitrate is decomposed and calcite formed. Subsequently, calcite is decarburized, and the remaining phosphate groups react with calcium, increasing the amount of nanocrystalline apatite domains. Above the Tg, the crystallinity of these phases is increased, other phases such combeita and β-cristobalite are easily identified among the products crystallization, occurring in independent events. Therefore, it was possible to propose a mechanism for crystallization of apatite below the Tg became clear that the sol-gel process produces, in fact, suitable conditions for crystallization even during the initial formation of bioglass at low temperatures and without any contact with biological fluids. The dissolution assay showed that there is no apparent change for different levels of MgO inserted, and that along the immersion period, the glass will decompose with the release of SiO44- while an apatite layer is being formed on the surface by deposition Ca2+, Mg2+ and PO43-.